ENSURING OF DOCUMENTS OF STRUGGLE OF THE SECOND UPR AGAINST THE JEWISH POGROMS - Лазарович, М. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Normative documents of authority Second UPR on maintenance of the right of citizens for a life are investigated. Efficiency of such means of struggle against pogroms are analysed. It is summed up, that through dominating anarchy taken measures quite often remained declarative.